2020
DOI: 10.1016/j.petrol.2019.106505
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling of methane hydrate dissociation under thermal stimulation

Abstract: In this study, a one-dimensional analytical model to describe heat and mass transfer during methane hydrate dissociation under thermal stimulation in porous media has been developed. The model is based on a similarity solution that considers a moving dissociation boundary which separates the dissociated zone containing produced gas and water from the un-dissociated zone containing only methane hydrate. The results of temperature distribution, pressure distribution, energy efficiency, and parametric study consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 54 publications
(75 reference statements)
3
13
0
Order By: Relevance
“…These results are in line with those reported by Roostaie and Leonenko [79], mainly because the temperature at the wellbore was not constant in their work due to the heat conduction through the wellbore structure. In accordance with the present results, a study by Tsimpanogiannis and Lichtner [29], who built a semi-analytical model for hydrate dissociation, demonstrated that increasing the temperature of the wellbore raised the pressure at the interface.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in line with those reported by Roostaie and Leonenko [79], mainly because the temperature at the wellbore was not constant in their work due to the heat conduction through the wellbore structure. In accordance with the present results, a study by Tsimpanogiannis and Lichtner [29], who built a semi-analytical model for hydrate dissociation, demonstrated that increasing the temperature of the wellbore raised the pressure at the interface.…”
Section: Resultssupporting
confidence: 93%
“…Selim and Sloan [62] and Roostaie and Leonenko [79] performed a similar parametric study and reported similar results for the rate of dissociation (Figure 8). Zhao et al [117] mathematically showed that increasing the thermal conductivity had a direct positive effect on a dissociation process based on thermal stimulation.…”
Section: Figures 9a and 9b Clearly Show The Direct Relation Between Esupporting
confidence: 56%
See 2 more Smart Citations
“…The analytical works conducted about the hydrate dissociation to present [47,[49][50][51] have not considered the impact of wellbore geometry and the associated structure (i.e., wellbore radius and the associated outer layers) on MH dissociation upon thermal stimulation by wellbore heating, which might induce unreliability while comparing to experiments or field works. Recently, Roostaie and Leonenko [52] mathematically overcame this gap of knowledge and showed that the wellbore structure, consisting of layers: casing, gravel, and cement, can also affect the interactions in the reservoir and the efficiency of the process upon thermal stimulation. They designed an analytical semi-infinite 1D model and verified it against previous numerical and experimental works.…”
Section: Introductionmentioning
confidence: 99%